2018
DOI: 10.1039/c8qo00219c
|View full text |Cite
|
Sign up to set email alerts
|

Visible light photoredox catalysis: conversion of a mixture of thiophenols and nitriles into 2-substituted benzothiazoles via consecutive C–S and C–N bond formation reactions

Abstract: A novel, visible-light-mediated method for the synthesis of 2-substituted benzothiazoles from thiophenols and alkyl/aryl nitriles in the presence of eosin Y under air atmosphere is disclosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…In 2018, Natarajan and co-workers disclosed a photocatalytic system for the modular synthesis of 2-substituted benzothiazoles from nitriles and thiophenols ( Scheme 238 ). 630 Contrary to many literature methods for the preparation of these scaffolds, which rely upon intramolecular S N Ar or cyclization of 2-aminothiophenols onto carboxylic acid derivatives, 631 Natarajan’s method obviates the need for pre-installed reactive functionality. Using a combination of thiophenol, nitrile, and EY as a photocatalyst in DMSO under air with green-light irradiation, the authors demonstrated 21 examples of benzothiazole synthesis, with good to excellent yields (68–92%).…”
Section: S -Centered Radical Generation From S–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…In 2018, Natarajan and co-workers disclosed a photocatalytic system for the modular synthesis of 2-substituted benzothiazoles from nitriles and thiophenols ( Scheme 238 ). 630 Contrary to many literature methods for the preparation of these scaffolds, which rely upon intramolecular S N Ar or cyclization of 2-aminothiophenols onto carboxylic acid derivatives, 631 Natarajan’s method obviates the need for pre-installed reactive functionality. Using a combination of thiophenol, nitrile, and EY as a photocatalyst in DMSO under air with green-light irradiation, the authors demonstrated 21 examples of benzothiazole synthesis, with good to excellent yields (68–92%).…”
Section: S -Centered Radical Generation From S–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…10 More recently, a visible-light photoredox catalysis for the synthesis of 2-substituted benzothiazoles was reported by Natarajan et al using Eosin Y as a photocatalyst. 11 However, a visible-light-mediated reaction does not necessarily need a photocatalyst. The ground-state association between the electron-rich donor (a nucleophile or reducing agent) and an electron-poor acceptor (an electrophile or oxidizing agent) can generate an electron donor−acceptor (EDA) or charge-transfer (CT) complex which can absorb the visible light and undergo photoexcitation to transfer an electron.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fu et al have developed a general and efficient visible-light photoredox cross-coupling of aryl halides with arenethiols at room temperature using [fac-Ir­(ppy) 3 ] as the photocatalyst . More recently, a visible-light photoredox catalysis for the synthesis of 2-substituted benzothiazoles was reported by Natarajan et al using Eosin Y as a photocatalyst …”
Section: Introductionmentioning
confidence: 99%
“…2B, in the nucleophilic addition of nitriles, the most reported reaction partners have been focused on the highly reactive nitrogen, [44][45][46][47][48][49][50][51][52] oxygen, [53][54][55][56][57][58][59][60][61] and sulfur nucleophiles till now. [62][63][64] For carbon pronucleophiles, the related studies are only limited to sp, sp 2 , and sp 3 with α-electron withdrawing group (i.e. cyano, carbonyl, ester groups) carbons, though some elegant work has been made by using transition metal catalysts.…”
Section: Introductionmentioning
confidence: 99%